Kurikulum Keterampilan Berbicara Bahasa Arab Pada Program ‘Tajawwal” Khusus tingkat Pemula di Pondok Pesantren Miftahul Ulum Panyeppen Pamekasan - M. Mansyur; Makmun (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The research aims to determine the application and problems of the Arabic speaking skills curriculum in the special beginner level tajawwal program at the Miftahul Ulum Pemeppen Pamekasan Islamic boarding school. This research uses a qualitative approach with a case study type. The data collection techniques used were interviews, observation and documentation as well as data analysis using interactive analysis techniques including presentation, analysis and drawing conclusions. The results of this research show that the implementation of the Arabic speech skills curriculum in the special beginner level tajawwal program at the Miftahul Ulum Pemekpen Pamekasan Islamic boarding school includes planning, implementation and evaluation and the problems felt in this implementation include two elements, namely internal and external.